The distribution of nutrients, dissolved oxygen and chlorophyll a in the upper Gulf of Nicoya, Costa Rica, a tropical estuary - Jaime Palter; Sandra León Coto; Daniel Ballestero (Revista de Biología Tropical, 2007)
in the Gulf of Nicoya on the Pacific Coast of Costa Rica, nutrient rich equatorial subsurface water (ESW) is upwelled in much of the lower gulf. These offshore waters are often regarded as the major source of nutrients to the gulf. However, for most of the year, the ESW has little influence on the nutrient content of the upper gulf, which has a distinct character from the lower gulf. The upper gulf, extending 40 km north of the restriction between Puntarenas Peninsula and San Lucas island, is bordered primarily by mangrove swamps, is less than 20 m deep, and is less saline than the lower gulf. We surveyed the upper gulf for dissolved inorganic nitrogen, phosphate, silicate, dissolved oxygen, and chlorophyll in November 2000, January and July 2001. All nutrients are more concentrated in the upper gulf during the rainy and transitional seasons than the dry season, significantly so for phosphate and silicate. Throughout the year, nutrients tend to be much more concentrated in the less saline water of the upper gulf. This trend indicates that discharge from the Tempisque River predominantly controls spatial and temporal nutrient variability in the upper gulf. However, nutrient rich ESW, upwelled offshore and mixed to form a mid-temperature intermediate water, may enter the inner gulf to provide an important secondary source of nutrients during the dry season. Rev. Biol. Trop. 55 (2): 427-436. Epub 2007 June, 29. Las aguas subsuperficiales ecuatoriales (ESW) que entran por la parte externa del Golfo de Nicoya de Costa Rica, se consideran una fuente importante de nutrientes para el estuario. Sin embargo, durante la mayoría del año las ESW tiene una influencia pequeña en la parte interna del golfo, que es oceanográfica y biológicamente diferente de la parte externa. La parte interna está ubicada desde la península de Puntarenas hasta la boca del Río Tempisque, 40 km al norte; es un área que se caracteriza por un importante aporte de agua dulce, está rodeada de manglares y tiene menos de 20 m de profundidad. En este estudio se midieron concentraciones de nitrato, nitrito, fosfato, silica-to, oxígeno disuelto y clorofila a en la parte interna del golfo en noviembre 2000, enero y julio 2001. Todos los nutrientes están concentrados en la parte interna del golfo durante la época lluviosa y de transición, y las concentraciones de fosfatos y silicatos son significantivamente diferentes respecto a las concentraciones en época seca. Durante todo el año los nutrientes muestran concentraciones mayores en las aguas más dulces cerca el Río Tempisque. Esto indica que las descargas del Río Tempisque dominan la variabilidad espacial y temporal en la parte interna. Además, los vientos alisios inducen la surgencia de ESW durante la estación seca, constituyendo una posible fuente secundaria de nutrientes durante esta época.